Perencanaan Lanskap Kebun Bergizi pada Lahan Sempit Kampus Kartini Universitas Kristen Satya Wacana Salatiga - Tusanto; Alfred Jansen Sutrisno (http://arl.faperta.ipb.ac.id/, 2023)
Kartini Campus has a land that has not been utilized well. That land has medium extent but can be utilized effectively. One of the utilization that can be conducted is agricultural activities in narrow land. As of this research tried to make narrow land agricultural model that can be used to fulfill nutritional food needs of dormitory students. The research methods are calculate the area that can be utilized with direct measurement, calculate the nutrition needs of students by identifying and calculate the body weight divided by body weight standard based on age and gender, then multiplied by nutritional needs standard. Determine the type of plants by adjusting with the climate condition and nutritional needs. Research result show that there are 8 points that can be utilized for agricultural activities with total area is ± 3.450,94 m2 (1) Block A (± 387,9 m2); (2) Block B (± 1.541,2 m2); (3) Block C (± 326,6 m2); (4) Block D (± 379,5 m2) (5) Block E (± 114.04 m2); (6) Block F (± 293,8 m2); (7) Block G (± 298.8 m2); and (7) Block H (± 109,1 m2). Nutritional needs of students is nutritional adequacy average of Kartini 11A dormitory students for energy ±2.489,525 kcal, protein 58,998 g, fat 83,069 g, and carbohydrate 342,285 g. So that there are several types of plants that are developed which are fruit plants (papaya) and vegetable plants (mustard, long beans, kale, spinach, and eggplant).